Management Protocols and Surgical Outcomes for Pediatric Intussusception : A Literature Review - Wahyu Agus Prastyo; Artha Investari Nugraheni (International Medical Journal Corp. Ltd, 2025)
Background: The literature on pediatric intussusception highlights the complexities of diagnosis and management, underscoring the need for timely intervention to optimize outcomes. The articles reviewed provide a multifaceted perspective on the condition, detailing diagnostic techniques, management protocols, and surgical outcomes. Literature Review: The initial article emphasizes the idiopathic nature of pediatric intussusception, linking it primarily to viral infections and the hyperplasia of Peyer's patches (Gupta et al., 2010). This foundational understanding is crucial as it sets the stage for the subsequent discussions on imaging and intervention strategies. The advocacy for ultrasonography as the primary diagnostic tool (Dadlani et al., 2020) reflects a shift towards non-invasive methods, aligning with contemporary pediatric practices that prioritize patient safety. The systematic review consolidates these insights, emphasizing the efficacy of non-surgical interventions and the necessity of surgical options when initial methods fail (Ali Attoun et al., 2023). It also discusses the role of adjunct therapies, such as dexamethasone, which reflects an evolving approach to treatment that integrates pharmacological support with traditional techniques. This distinction is critical for surgical planning, as it informs whether non-operative reduction or surgical intervention is warranted. The importance of timely diagnosis and intervention is further reinforced by the findings on idiopathic intussusception, where non-operative methods, such as pneumatic enemas, are shown to be effective (Alnamshan et al., 2023). Conclusion: In conclusion, the reviewed literature collectively underscores the critical importance of accurate diagnosis and timely intervention in managing pediatric intussusception. The evolution of management protocols, from non-invasive imaging to surgical interventions, illustrates a comprehensive approach that prioritizes patient outcomes. Continued research and the development of standardized management algorithms will be essential in further refining these protocols to enhance surgical outcomes for pediatric patients.